Balancing Efficacy and Tolerability: A Prospective Cohort Study of Oral and Intravenous Methylprednisolone for Active Graves' Ophthalmopathy in an Indonesian Tertiary Care Center - Mardijas Efendi; Hendriati; Pattih Primasakti; Yolanda Wulandari Erwen (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: In managing active, moderate-to-severe Graves' Ophthalmopathy (GO), a notable gap often exists between treatment efficacy in controlled trials and effectiveness in real-world practice. High-dose corticosteroids are standard, but the choice between intravenous (IV) and oral routes involves a complex trade-off between efficacy, tolerability, and practicality, particularly in diverse populations. Methods: This single-center, pragmatic, prospective cohort study was conducted at a tertiary hospital in Indonesia from March 2023 to March 2024. Thirty-six GO patients were treated with either IV pulse or daily oral methylprednisolone based on a shared clinical decision-making process. The primary outcome was the change in proptosis. To address the non-randomized design and control for selection bias, a propensity score-adjusted Analysis of Covariance (ANCOVA) was used to compare treatment effectiveness. Results: Baseline analysis revealed that patients selected for IV therapy had significantly more severe proptosis. Both unadjusted and adjusted analyses showed that each regimen resulted in a significant reduction in proptosis from baseline (p < 0.01). In the primary, propensity score-adjusted analysis, no statistically significant difference was detected in the degree of proptosis reduction between the IV and oral groups. However, the tolerability profiles were profoundly different; patients in the oral group experienced a significantly higher incidence of adverse events, including dyspepsia (66.7%) and Cushingoid features (55.6%), compared to a single case of transient hypokalemia in the IV group. Conclusion: In this real-world setting, after statistically controlling for baseline severity, both IV and oral methylprednisolone demonstrated comparable effectiveness in reducing proptosis. However, the intravenous route was associated with a vastly superior safety profile. These findings underscore the critical importance of tolerability in clinical decision-making and support the continued recommendation of IV pulse therapy as the first-line treatment.